Phytoremediation of Ammonia, BOD, COD, and TSS with Water Hyacinth (Eichhornia crassipes) for Wastewater - Prinajati, Purnomosutji Dyah; Hanaseta, Evelyne; Sasongko, Budi (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
Water hyacinth (Eichhornia crassipes) is a typical aquatic plant with several physical characteristics such as the leaves of water hyacinth are glossy and ovoid to circular in shape, with spongy petioles that provide buoyancy. The plant is widely known for its rapid proliferation, with its population being able to double in just 12 days. The Pulo Gebang Fecal Sludge Treatment Plant (STP) is a facility that treats sewage from people’s homes or centralized treatment plants. However, the treated water often does not meet quality standards. To solve this problem, a sustainable and environmentally friendly wastewater treatment method called phytoremediation was chosen. Phytoremediation involves the use of plants to remove pollutants from wastewater, offering cost efficiency, minimum energy requirements, and conservation of soil biological activity. Water hyacinth (Eichhornia crassipes) was chosen for its quality and ability to degrade penetrant substances. Phytoremediation was carried out in batch form with 3 variations of testing time, namely 5, 10 and 15 days. The study found that phytoremediation using water hyacinth significantly reduced ammonia levels, BOD, COD, and TSS parameters, with the most effective contact time being 10 days. This shows that the phytoremediation method using water hyacinth is effective in reducing contaminant levels and can be a sustainable solution for treating domestic wastewater at IPLT Pulo Gebang.